A Tri- State Filter for the Removal of Salt and Pepper Noise in Mammogram Images. - Ramachandran, Varatharajan; Kishorebabu, Vasanth (Journal of Medical Systems, 2019)
A new algorithm which uses tree based decision and tri-state non linear values to eliminate high density outlier noise in mammogram images is proposed. The proposed algorithm uses the number of non noisy pixels in the current processing vicinity as values in the decision tree. Tri-state values such as unsymmetrical truncated median or modified Winsorized mean or midpoint replaces the corrupted pixel based on the decision tree in the current processing kernel. The algorithm exhibits good PSNR, IEF, low MSE and High structural preservation property even after removing high density noise. The performance of the proposed algorithm was also found good visually. The Key aspect of the work is the combination of tree based decision and tri-state non linear values which preserves the information content of images that are required for further processing.